Primary Nasal Tuberculosis in a 10-Year-Old Girl - Murat Özer; Yasemin Özsurekçi; Ali Bülent Cengiz; Uğur Özçelik; Ebru Yalçın; Özay Gököz (Canadian Journal of Infectious Diseases and Medical Microbiology)
Nasal tuberculosis is a rare clinical entity which mainly presents in elderly people. Nasal tuberculosis has always been considered to be secondary to tuberculosis of the lungs, and in rare instances it is a primary infection, usually when mycobacteria are inhaled. We describe the case of a 10-year-old girl who was successfully treated for primary nasal tuberculosis. This patient is one of the very few children who have been reported to have primary nasal tuberculosis.